EFEKTIFITAS TEKNIK TANDUR (TUMBUHKAN, ALAMI, NAMAI, DEMONSTRASI, ULANGI DAN RAYAKAN) PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM PADA KELAS V SD NEGERI 37 OKU - Ade Vidianti (Jurnal Educative: Journal of Educational Studies, 2018)
Abstract: The aim of this study was to know the effectiveness of TANDUR technique (Tumbuhkan, Alami, Namai, Demonstrasi, Ulangi dan Rayakan) on the natural science subject at the fifth grade students of SD Negeri 37 OKU. The population in this exsperimental study was fifth grade students of SD163 OKU, and sample ware V.a and V.b. the data analized by using normality, homogenity, and also t-test. The results of this study was the value of t-obtain from normality test in TANDUR technique was -0,494, t-obtain in PAKEM techique was 0,1142. The value of the t-tabel was 0,05 for N=46 and 24 was 0,161 and 0,19. It concluded that TANDUR and PAKEM trchnique were below L-table so tehe data distribution was normal. The value of kai squared in dk table (2-1)=1, getting 3,841 on significant level 0,05. The value of kai squared was -8,197. It means that the T-obtain of kai squared was lower that t-table of kai squared or -8,197 2,06, so it could be concluded that TANDUR technique was more effective that PAKEM. In summary, the application of TANDUR technique was effective for natural science subject at the fifth grade students of SD Negeri 37 OKU. Keywords: Effectivity, Technique TANDUR, Learning Out Come.